Breathprinting Reveals Malaria-Associated Biomarkers and Mosquito Attractants. (3rd February 2018) - Schaber, Chad L; Katta, Nalin; Bollinger, Lucy B; Mwale, Mwawi; Mlotha-Mitole, Rachel; Trehan, Indi; Raman, Barani; Odom John, Audrey R
Abstract : Untargeted metabolomics of breath samples was performed for pediatric patients in Malawi with and those without malaria. A combination of 6 breath compounds could be used to diagnose malarial infection with 83% accuracy. Additionally, infection corresponded with higher levels of 2 mosquito-attractant terpenes. Abstract: Current evidence suggests that malarial infection could alter metabolites in the breath of patients, a phenomenon that could be exploited to create a breath-based diagnostic test. However, no study has explored this in a clinical setting. To investigate whether natural human malarial infection leads to a characteristic breath profile, we performed a field study in Malawi. Breath volatiles from children with and those without uncomplicated falciparum malaria were analyzed by thermal desorption–gas chromatography/mass spectrometry. Using an unbiased, correlation-based analysis, we found that children with malaria have a distinct shift in overall breath composition. Highly accurate classification of infection status was achieved with a suite of 6 compounds. In addition, we found that infection correlates with significantly higher breath levels of 2 mosquito-attractant terpenes, α-pinene and 3-carene. These findings attest to the viability of breath analysis for malaria diagnosis, identify candidate biomarkers, and identify plausible chemical mediators for increased mosquito attraction to patients infected with malaria parasites.